Kajian kecenderungan penyakit DBD di Kota Bitung tahun 2015-2017 - Mokolensang, Gerry Octapian; Rombot, Dina V.; Siagian, Iyone E. T. (UNIVERSITAS SAM RATULANGI, 2018)
Background: Dengue Hemorrhagic Fever is a disease caused by dengue virus infection that is still a public health problem. This disease is almost found in almost all parts of the world, especially in tropical and subtropical countries both as endemic and epidemic diseases. Aim: To obtain information about dengue in the city of Bitung.Method: This study is a descriptive study with a cross sectional studies and retrospective approach.Results: Results were obtained from 2015-2017 where there were 346 DHF cases and 8 cases of death.Conclusion: In 2015-2017 there was a decrease in the number of cases from 124 cases to 110 cases, meaning that the role of health workers with the community was effective, but cases of deaths from DHF have not been resolved so that the death rate increased from 2 fatalities to 5 deaths.